Evaluation of light filtration in portable dark chambers and its influence on the visibility of radiographic films (Research, Society and Development, 2021)
Introduction: RDC No. 330 is the process for using a portable camera for processing intraoral radiographs, provided that it is made of opaque material and that it has a stopwatch and thermometer to perform radiographic processing using the time x temperature method. The aim of this study was to evaluate the filtration of light in portable cameras with viewfinder and without viewfinder and its influence on the veiling of periapical radiographic films. Methodology: This experimental study tested four portable darkrooms from brands NMartins.e Essence Dental VH with visor, Manoel PG all red acrylic and one without a visor by Delta Del Grandi. For control, a completely dark room was used. The periapical films used were from group E (Carestream and AGFA) and processed with developer and fixer solutions for three minutes in the developer, 20 seconds in the intermediate bath (water), six minutes in the fixer and 10 minutes in the final bath. After drying, such radiographs were digitized. The measurement of the pixel corresponding to the optical density of the darkest area was performed, obtaining a value between 0 (black) and 255 (white) in an 8-bit computer. Result: In the darkrooms ManoelPG and NMartins, the image of the coin was visible, demonstrating light veiling in both films. In the EssenceVH portable darkroom, there was total blurring, and it was not possible to visualize the contrast of the coin image, nor to measure the density. Conclusion: The darkroom without a viewfinder proved to be suitable for radiographic processing, however, as with viewfinder or fully acrylic, they did not filter out, causing the light to be blurred.